A Novel Pd‐Catalysed Annulation Reaction for the Syntheses of Pyrroloindoles and Pyrroloquinolines. Issue 1 (25th November 2015) - Dethe, Dattatraya H.; Boda, Raghavender
Abstract: Pd‐catalysed annulation reactions between indole derivatives and internal alkyne esters leading to various pyrrolo[1, 2‐ a ]indoles and pyrroloquinolines have been developed. The strategy involves an intermolecular addition of the indole nitrogen on to the internal alkyne ester followed by an intramolecular insertion of a vinyl–palladium complex into the carbonyl group. This method offers a facile and practical approach to pyrrolo[1, 2‐ a ]indoles and pyrroloquinolines. Abstract : One‐pot recipe! Pd‐catalysed annulation reactions between indole derivatives and internal alkyne esters leading to various pyrrolo[1, 2‐ a ]indoles and pyrroloquinolines have been developed (see scheme). The strategy involves an intermolecular addition of the indole nitrogen on to the internal alkyne ester followed by an intramolecular insertion of a vinyl–palladium complex into the carbonyl group.